MODELING REAL ESTATE MARKET: FORECASTING THE PRICE OF A SQUARE - Natalya V. Kontsevaya (Статистика и экономика, 2016)
The possibility of forecasting indicators of the real estate market. An approach based on the use of lag variables, where the lag time is determined by analyzing the dynamics of relative error. The result is a leading indicator. Forecasted assessment of the near future the price per square meter in Moscow.